The scope of criminal liability for misappropriation of authorship in EU countries: comparative analysis - Steponavičiūtė, Ramunė (Vilnius University Open Series, 2020)
Intellectual property legal protection is undoubtedly one of the most important factors and conditions of effective economic, social and cultural development in modern society. According to researchers, absolute majority of countries in the world have set criminal liability for certain crimes against intellectual property rights, including all of the European Union (hereinafter – EU) countries. One of those crimes is misappropriation of authorship. Yet the criminal laws of EU countries criminalise misappropriation of authorship very differently - some protect not only author rights but also related rights, the conditions for criminal liability in the general corpus delicti are of a very different scope as well as the punishments for those crimes differ significantly. This analysis will present the scope of criminal liability in all the EU countries, including the reasons why, as well as will try to find the answer whether ways of coping with these difficulties exist.